3.9k views
3 votes
So I don't understand how V = lwh (h).... the topic is literal equations.

User BloodAxe
by
6.2k points

1 Answer

4 votes

1) Solving in terms of h

V = lwh Divide both sides by h


\begin{gathered} V\text{ = lwh} \\ (V)/(h)=(lwh)/(h) \\ (V)/(h)\text{ =}lw\text{ Cross multiply} \\ hlw=V\text{ Divide both sides by lw} \\ (hlw)/(lw)=\text{ }(V)/(lw) \\ h\text{ = }(V)/(lw) \end{gathered}

So rearranging that equation we can find h, in terms of V, and l and w.

If we want to solve in terms of l, or w, we'll proceed similarly to isolate the variable we want on the left side, and the other terms on the right side.

User Michael Capobianco
by
5.5k points